Microstructure of pyrolyzing RTV silicone. (January 2023) - Oruganti, Sreevishnu; Mansour, Nagi N.; Panesi, Marco; Panerai, Francesco
Highlights: Mass loss, foaming and microstructure evolution of RTV as a function of temperature are discussed. Pore size distribution and porosity of RTV were measured for charred RTV. An intumescence model capturing all the observed multiphysical phenomena is proposed. Abstract: This works discusses the high temperature decomposition of Room Temperature Vulcanized (RTV) silicone, an adhesive material used as a gap filler in ablative heatshield for planetary atmospheric entry, and in fire-protection applications. The high temperature behavior of RTV is characterized by intumescence, shrinkage, foaming and formation of a glassy char. In heatshield applications, these phenomena lead to a mismatch between the ablative response of RTV and that of carbon-phenolic tiles, posing numerous design challenges such as tile layout selection, installation of heatshield sensors, prediction of laminar-to-turbulence transition and assessment of heatshield robustness. The ablation response of RTV is not modeled in current design tools because of the lack of data on its high temperature behavior. In this paper, thermogravimetric analysis was conducted to quantify the mass-loss of RTV during pyrolysis, as a function of heating rate. Samples were imaged using environmental scanning electron microscopy at high temperature to observe the microstructural evolution of RTV during charring. Helium pycnometry, mercury intrusion porosimetry and nitrogen adsorption techniques, combined with micro-tomography imaging, were used to quantify the pore size distribution and porosity of charred RTV. Results show that the porosity of charred RTV is about 82% and that the predominant pore sizes are 2, 23, 39 and 98 microns. The net volumetric swelling due to pyrolysis of the material was found to be 10% when heated to 1000  ° C. Physical phenomena occurring during high temperature decomposition are discussed based on the experimental observations.